2023
DOI: 10.1038/s41418-023-01126-z
|View full text |Cite|
|
Sign up to set email alerts
|

S100 family proteins are linked to organoid morphology and EMT in pancreatic cancer

Abstract: Epithelial-mesenchymal transition (EMT) is a continuum that includes epithelial, partial EMT, and mesenchymal states, each of which is associated with cancer progression, invasive capabilities, and ultimately, metastasis. We used a lineage-traced sporadic model of pancreatic cancer to generate a murine organoid biobank from primary and secondary tumors, including sublines that underwent partial EMT and complete EMT. Using an unbiased proteomics approach, we found that organoid morphology predicts the EMT state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…It may be at the final spectrum of the basal-like cell state, as others classified it in metastatic samples (Basal A) [6]. These observations are in agreement with recent publications [25,33], where S100 family proteins are particularly linked to EMT and metastasis [22]. The fact that S100A2 mRNA and protein do not correlate most likely stems from a delayed protein synthesis, as reported during short-term cell adaptation and the process of differentiation state transitioning [34,35], while other transcriptional and translational effects cannot be excluded.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It may be at the final spectrum of the basal-like cell state, as others classified it in metastatic samples (Basal A) [6]. These observations are in agreement with recent publications [25,33], where S100 family proteins are particularly linked to EMT and metastasis [22]. The fact that S100A2 mRNA and protein do not correlate most likely stems from a delayed protein synthesis, as reported during short-term cell adaptation and the process of differentiation state transitioning [34,35], while other transcriptional and translational effects cannot be excluded.…”
Section: Discussionsupporting
confidence: 90%
“…We also included protein markers of basal-like tumours (i.e. deltaNp63 alias P40, KRT5, and S100A2) used previously as single markers for subtype calling to replace the transcriptomic classification in histological analysis [21][22][23][24]. Of these, we found a statistically positive correlation only between S100A2 and KRAS G12D (Figure 4B,D).…”
Section: Intra-patient Inter-ductal and Intra-ductal Spatial Heteroge...mentioning
confidence: 90%
See 1 more Smart Citation
“…The group induced malignant transformation of healthy organoids by knocking out the PCa-specific genes Pten, Rb1, and Tp53 in vitro and showed that over time the resulting tumoroids acquired an intermediate luminal-basal phenotype. An epithelial to mesenchymal (EMT) signature was further supporting tumoroid plasticity, a phenomenon that has recently also been investigated in pancreatic cancer (PaCa) organoids [96]. Of note, the authors reported that the PCa tumoroid plasticity was further induced by androgen ablation (the suppression or blockage of the androgen pathway using chemical compounds), the most common treatment for PCa, and identified JAK/STAT and FGFR signaling as the main drivers [68].…”
Section: Organoids For Cancer Research: Tumoroidsmentioning
confidence: 87%
“…EMT is one of the characteristics of solid tumor metastasis, and EMT phenotype also exists in many hematological tumors. A study found that S100A4 was associated with the low survival rate of pancreatic cancer, and TGFβ1 promoted EMT and increased invasiveness by up-regulating S100A4 expression level [ 38 ]. In addition, CXCR4 was highly expressed in MM patients with extramedullary invasion, which promoted cell spread and metastasis by inducing EMT phenotype [ 39 ].…”
Section: Discussionmentioning
confidence: 99%